What's in an Outgroup? The Impact of Outgroup Choice on the Phylogenetic Position of Thalattosuchia (Crocodylomorpha) and the Origin of Crocodyliformes - Wilberg, Eric W (Systematic biology, 2015)
Outgroup sampling is a central issue in phylogenetic analysis. However, good justification is rarely given for outgroup selection in published analyses. Recent advances in our understanding of archosaur phylogeny suggest that many previous studies of crocodylomorph and crocodyliform relationships have rooted trees on outgroup taxa that are only very distantly related to the ingroup (e.g., Gracilisuchus stipanicicorum), or might actually belong within the ingroup. Thalattosuchia, a group of Mesozoic marine crocodylomorphs, has a controversial phylogenetic position--they are recovered as either the sister group to Crocodyliformes, in a basal position within Crocodyliformes, or nested high in the crocodyliform tree. Thalattosuchians lack several crocodyliform apomorphies, but share several character states with derived long-snouted forms with a similar ecological habit, suggesting their derived position may be the result of convergent evolution. Several of these "shared" characters may result from ambiguously worded character state definitions--structures that are superficially similar but anatomically different in detail are identically coded. A new analysis of crocodylomorphs with increased outgroup sampling recovers Thalattosuchia as the sister group to Crocodyliformes, distantly related to long-snouted crocodyliforms. I also demonstrate that expanding the outgroup sampling of previously published matrices results in the recovery of thalattosuchians as sister to Crocodyliformes. The exclusion of thalattosuchians from Crocodyliformes has numerous implications for large-scale evolutionary trends within the group, including extensive convergence in the evolution of the secondary palate characteristic of the group. These results demonstrate the importance of careful outgroup sampling and character construction, and their profound effect on the position of labile clades.